Editorial for proceedings papers - Steven Verjans; Kia Ng; David Hawkridge (Association for Learning Technology, 2011)
Here are the proceedings of the 2011 ALT Conference ‘‘Thriving in a colder and more challenging climate’’. Proceedings papers report on a piece of research, possibly in its early stages, or they can be ‘‘thoughtpieces’’ which state a point of view or summarise an area of work, perhaps giving new insights.